A fight for the soul of public education : the story of the Chicago teachers strike - Ashby, Steven K.; Bruno, Robert, 1955- (ILR Press, an imprint of Cornell University Press, 2016)
In reaction to the changes imposed on public schools across the country in the name of "education reform," the Chicago Teachers Union redefined its traditional role and waged a multidimensional fight that produced a community-wide school strike and transformed the scope of collective bargaining into arenas that few labor relations experts thought possible. Using interviews, first-person accounts, participant observation, union documents, and media reports, Steven K. Ashby and Robert Bruno tell the story of the 2012 strike that shut down the Chicago school system for seven days. A Fight for the Soul of Public Education takes into account two overlapping, parallel, and equally important stories. One is a grassroots story of worker activism told from the perspective of rank-and-file union members and their community supporters. Ashby and Bruno provide a detailed account of how the strike became an international cause when other teachers unions had largely surrendered to corporate-driven education reform. The second story describes the role of state and national politics in imposing educational governance changes on public schools and draconian limitations on union bargaining rights. It includes a detailed account of the actual bargaining process revealing the mundane and the transcendental strategies of both school board and union representatives. -- Provided by publisher